Analisis Tentang Faktor-Faktor yang Melatarbelakangi Pemilihan Karir bagi Mahasiswa Akuntansi: Antara Akuntan Publik Versus Non Akuntan Publik - Harris, Lutfi; Djamhuri, Ali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2001)
This study compares accounting students who choose a career as public accountant (Group l)to those students who did not (Group II). A questioncdre consisting of 18 questions concerning five career selection factors were addressed, namely, intrinsic values of job, flexibility, job market opportunities, perceived benefit of being a public accountant, and perceived cost of being a public accountant. By employing a survey method to 148 accounting students of Brawijaya University Malang and Airlangga University Surabaya, t- test were used to compare responses of students selecting the public accountant and those selecting non-public accountant career. Multivariate Discriminant Analysis was also used to assess the ability of five factors to distinguish between these two groups. The results indicate that based on their average score, those selecting public accountant are more concerned with the above five factors. However, based on the independent sample t-test, there are only two questions resulting in scores that were statistically significant: (l)job market opportunity that is as a job with long-term earning and (2) flexibility that public accountant is a flexible job. These findings were also supported by the analytical result from multivariate discriminant analysis (MDA). The highest explanatory power variable differentiating the two groups is job market opportunity. Key words: carrier selection, accounting students, public and non public accountants, intrinsic values, flexibility, job market opportunities.